2015
DOI: 10.1016/j.ceb.2015.06.007
|View full text |Cite|
|
Sign up to set email alerts
|

Filopodia in cell adhesion, 3D migration and cancer cell invasion

Abstract: This review discusses recent advances in our understanding of the role filopodia and filopodia-like structures in cell adhesion and three dimensional (3D) cell migration both in vitro and in vivo. In particular, we focus on recent advances demonstrating that filopodia are involved in substrate tethering and environment sensing in vivo. We further discuss the emerging role of filopodia and filopodial proteins in tumor dissemination as mounting in vitro, in vivo and clinical evidence suggest that filopodia drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
358
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 444 publications
(408 citation statements)
references
References 64 publications
23
358
0
Order By: Relevance
“…Filopodia are thin actin-based protrusions that extend from cells involved in cell adhesion and migration (Jacquemet et al, 2015). In 1961, Wolpert and Gustafson visualized filopodia in live sea urchin embryos at the blastula stage, resulting in behavior indicating that filopodia function as sensors of patterning information (Gustafson and Wolpert, 1961).…”
Section: Cytonemes Regulate the Distribution Of Signaling Proteinsmentioning
confidence: 99%
“…Filopodia are thin actin-based protrusions that extend from cells involved in cell adhesion and migration (Jacquemet et al, 2015). In 1961, Wolpert and Gustafson visualized filopodia in live sea urchin embryos at the blastula stage, resulting in behavior indicating that filopodia function as sensors of patterning information (Gustafson and Wolpert, 1961).…”
Section: Cytonemes Regulate the Distribution Of Signaling Proteinsmentioning
confidence: 99%
“…40 Cells migrating in the two-dimensional models often display only sparse filopodia, whereas in the threedimensional invasion model or in vivo, cells extensively use filopodia to probe the extracellular matrix and migrate. 41,42 Both cell lines exhibited mutations in PTEN, whereas U118 also revealed p53 mutation.…”
mentioning
confidence: 99%
“…Trophozoites, like other migratory cells (Yamaguchi and Condeelis, 2007; Jacquemet et al, 2015; Fritz-Laylin et al, 2017), showed filamentous actin in their membrane protrusions when stimulated in the MPGL, generating mainly long and short filipodia. The long filipodia did not show completely structured F-actin, possibly due to the fact that it was in the process of integration to stabilize the tubular filamentous structure (Karlsson et al, 2013).…”
Section: Discussionmentioning
confidence: 94%